School Social Work History: A Scoping Review - Ashley-Marie H. Daftary (International Journal of School Social Work, 2024)
The school social work (SSW) specialization has historically been and continues to be dominated by White women and critiqued for its lack of inclusion and use of western, race-neutral models to guide practice. In response to this criticism, and the Council of Social Work Education’s 2022 accreditation standards requiring programs to recognize the impact of white supremacy, the author completed a scoping review to identify common themes and gaps found in the literature describing SSW history, including if and how racism and white supremacy are discussed. Seventeen articles are included in this review. Common topics explored throughout the literature include a discussion of: 1. the Visiting Teachers Movement (VTM), 2. the influence of key figures, private agencies, and legislation on SSW practice, and 3. guiding models for SSW practice. Gaps included both a critical analysis and critiques of SSW history, and meaningful discussion of the impact of bias, racism, and white supremacy on the profession. Recommendations for future research and analysis are described.
Keywords: school social work history; scoping review; critical analysis; racism; white supremacy and bias